Muscle Fiber Conduction Velocity Correlates With the Age at Onset in Mild FSHD Cases - Beretta-Piccoli, Matteo; Negro, Massimo; Calanni, Luca; Berardinelli, Angela; Siciliano, Gabriele; Tupler, Rossella; Soldini, Emiliano; Cescon, Corrado; D’Antona, Giuseppe (Frontiers in Physiology, 2021)
A majority of patients with facioscapulohumeral muscular dystrophy (FSHD) report severe fatigue. The aim of this study was to explore whether fatigability during a performance task is related to the main clinical features of the disease in mildly affected patients. A total of 19 individuals with a molecular genetic-based diagnosis of FSHD (median D4Z4 deletion length of 27 kb) performed two isometric flexions of the dominant biceps brachii at 20% of their maximal voluntary contraction (MVC) for 2 min, and then at 60% MVC until exhaustion. Fatigability indices (average rectified value, mean frequency, conduction velocity, and fractal dimension) were extracted from the surface electromyogram (sEMG) signal, and their correlations with age, D4Z4 contraction length, perceived fatigability, and clinical disability score were analyzed. There were no significant correlations between fatigability and sociodemographic and clinical variables. Thus, in mild cases of FSHD, clinical features—especially D4Z4 contraction length—are unrelated to performance fatigability.